Influencer Vlogger Makanan, Ulasan Pelanggan Online, Pengiriman Makanan Online dan Suasana Restaurant terhadap Minat Beli Pelanggan di Sachon Pocha Mojokerto - Faren Kesita Gelioni; Ahfi Nova Ashriana; Rachmad Sholeh (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
In the culinary sector, digital marketing strategies play a crucial role in building consumer interest amid highly competitive markets and ever-evolving consumer behavior. This study aims to identify and analyze the influence of food vlogger influencers, online customer reviews, online food delivery services, and restaurant ambiance on customer purchasing interest at Sachon Pocha Mojokerto. The study employs a causal research design, with the population consisting of Sachon Pocha Mojokerto customers. The sample was determined using purposive sampling, involving 97 respondents. Data collection methods included online and offline questionnaires. Data analysis techniques used multiple linear regression analysis. The regression equation obtained from the study is Y = 0.434 X1 + 0.168 X2 + 0.150X3 + 0.245X4. The Food Vlogger Influencer variable (X1) significantly influences customer purchase interest (Y) at Sachon Pocha Mojokerto with a significance level of 0.000 < 0.05. Online Customer Reviews (X2) do not significantly influence customer purchase intent (Y) at Sachon Pocha Mojokerto, with a significance level of 0.127 > 0.05. Online Food Delivery (X3) does not significantly influence customer purchase intent (Y) at Sachon Pocha Mojokerto, with a significance level of 0.057 > 0.05. Restaurant Atmosphere (X4) has a significant effect on customer purchase interest (Y) at Sachon Pocha Mojokerto with a significance level of 0.035 < 0.05.